Reconstruction of Source-Based Waste Management Policy in Supporting Sustainable Tourism in Bali - Yohanes I Wayan Suryadi; Ni Luh Made Mahendrawati; I Gusti Bagus Suryawan (Warmadewa Press, 2026)
This study examines the reconstruction of source-based waste management policies in supporting sustainable tourism in Bali which faces major problems in the aspect of policy implementation. Although there have been various regulations, the existing regulations are still declarative, not yet operational, and have not been able to integrate the legal substance, institutional structure, and legal culture of the community. On the other hand, Bali has the strength of local values such as Tri Hita Karana and mutual cooperation that have not been fully institutionalized in the formal legal system, so waste management still depends on social awareness, not binding legal obligations. This study uses a normative juridical method with a legislative, conceptual, and comparative legal approach to practice in Japan, South Korea, and Singapore. The results of the study show the need for policy reconstruction through a hybrid legal system model that integrates state law, customary law, economic instruments, education, and technology. This model emphasizes strengthening operational norms, institutional integration, and the proportional role of traditional villages and tourism industry players. Thus, waste management not only improves the quality of the environment, but also strengthens the competitiveness of Bali's sustainable and ecologically just tourism.